Susceptibility of Leptospira serotypes against various antimicrobials by broth microdilution method - CHITRA, M ANANDA (The Indian Journal of Animal Sciences, 2013)
In developing countries like India, 90% of patients with leptospirosis have mild flu like symptoms and these patients are treated empirically for fever. Broth microdilution method using resazurin dye reduction assay was followed to test the susceptibility of 30 serovars of Leptospira to various antimicrobial drugs that are generally prescribed for fever in India in vitro. Among 19 antimicrobial drugs tested against Leptospira sp., erythromycin, azithromycin, cefatoxime, penicillin G, ampicillin, amoxycillin and levofloxacin produced MIC90 of below the limit of testing i.e.